Eksplorasi video youtube sebagai e-scaffolding afektif pada pembelajaran integral: Analisis konten kolom komentar - Zulfa Nur Jannah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
In the digital learning era, YouTube has become an alternative learning medium that potentially provides affective support during learning. This study aims to explore the role of YouTube videos as affective e-scaffolding in integral learning. The study employed a qualitative approach using content analysis and a netnographic approach. The data sources consisted of user comments on three integral learning videos selected through purposive sampling based on several criteria, namely long-duration videos, high view counts, active comment interactions, and systematic explanations of integral material. Data were collected through digital documentation and analyzed using the interactive model of Miles and Huberman,. The findings revealed three main indicators of affective e-scaffolding: anxiety reduction, increased motivation and self-efficacy, and frustration control. User comments demonstrated that YouTube videos not only facilitated conceptual understanding but also provided emotional support in overcoming learning obstacles in integrals. This study contributes to the development of digital scaffolding theory by emphasizing the importance of affective dimensions in technology-based mathematics learning.